Evidence of chloroplast capture in South American Nothofagus (subgenus Nothofagus, Nothofagaceae) - Acosta, María Cristina; Premoli Il'grande, Andrea Cecilia (Molecular Phylogenetics and Evolution)
Subgenus Nothofagus, although geographically restricted at present to temperate areas of South America, has captured much attention in discussions of plant biogeography due to its widespread distribution through Gondwanan continents during the Tertiary. However, phylogenetic relationships within the subgenus Nothofagus have not yet been resolved. We examined geographic patterns of intraspecific and interspecific genetic variation to detect whether incongruences in nuclear or plastid DNA phylogenies occur, in order to better understand the evolutionary history of the subgenus Nothofagus. We conducted spatially-explicit sampling at 10 distinct locations throughout the range of austral South American forests and sampled all present Nothofagus species. We used ITS and chloroplast DNA sequences to estimate phylogenetic relationships. A phylogeny constructed from nuclear genes resolved the subgenus Nothofagus as monophyletic. We found that N. antarctica was a sister to a clade of evergreen species (N. betuloides, N. dombeyi, and N. nitida), while N. pumilio likely diverged earlier. Nine cpDNA haplotypes were distinguished in the subgenus Nothofagus which were associated to geographic locations rather than to taxonomic relationships. This species-independent cpDNA phylogeographic structures within the subgenus Nothofagus may be related to repeated chloroplast capture events over geological time in Patagonia. Fil: Acosta, María Cristina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Córdoba. Instituto Multidisciplinario de Biología Vegetal (p); Argentina Fil: Premoli Il'grande, Andrea Cecilia. Universidad Nacional del Comahue; Argentina